Relationship Between Teachers' Attitudes and Knowledge About Epilepsy and Their Health Literacy and Health Anxiety. - Güneş, Nebahat Bora; Baş, Melike Taşdelen (Journal of Education & Research in Nursing / Hemşirelikte Eğitim ve Araştırma Dergisi, 2025)
Background: Epilepsy is a common neurological condition that can affect students in educational settings. Teachers' knowledge and attitudes toward epilepsy play a vital role in ensuring student safety and educational continuity. Aim: This study aimed to examine the relationship between teachers' health literacy, health anxiety, and their knowledge and attitudes toward epilepsy. Methods: A cross-sectional descriptive study was conducted among primary, middle, and high school teachers in Ankara, Türkiye. A total of 205 teachers were selected through simple random sampling. Data were collected using a sociodemographic questionnaire, Epilepsy Knowledge and Attitude Inventories, Short Health Anxiety Inventory, and Turkey Health Literacy Scale-32. Descriptive statistics, Pearson correlation, Student's t-test, and Chi-square tests were used for data analysis. Results: Participants had a mean age of 46.16±8.33 years and an average of 21.79±8.46 years of teaching experience; 75.6% were female. The mean scores on the epilepsy attitude and knowledge inventories were 41.32±5.32 and 8.26±2.95, respectively. Teachers with personal experiences, such as witnessing a seizure or having a family member with epilepsy, scored higher on epilepsy knowledge. Knowledge of epilepsy was negatively associated with the "negative consequences" subdimension of health anxiety and overall health literacy. Positive correlations were found between epilepsy attitudes and health literacy, while attitudes were negatively correlated with health anxiety. Conclusion: Training programs should be implemented to improve teachers' knowledge of epilepsy and their first aid skills, especially for those without prior experience. These programs should address practical aspects of epilepsy, including symptoms, seizure types, and appropriate interventions. Additionally, they should offer stress management strategies to enhance teachers' confidence and preparedness.